PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI - Suryani E.42008039, Tatik (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of this research is "The Effect of   the work environment to employee performence In Sanggau Ledo District Office in Bengkayang Regency. This research is supposed to  know whether non physical environment  affects employee performance Sanggau Ledo District Office in Bengkayang Regency. The title of this research concerns was brought up based on the evolving non physical environment affects employee performance in the ministry. This research is quantitative research using simple linear regression statistical test. Based on the results of the study, obtained the following regression equation: Y = 8.624 + 1.058X Based on the analysis of statistical data, indicators in this study are valid and variables are reliable. The results indicate that the hypothesis Fcount greater than F table (38.577> 4.54) with a significance level of 0.000 so that the hypothesis in this study accepted that there is a positive and significant correlation between non physical environment to employee performance. Key Word : Non Physical Environment And Employee Performence